Early tax education: Could it change the future compliance behavior? - Albert Albert; Rien Agustin Fadjarenie (International Journal of Evaluation and Research in Education (IJERE), 2022)
Many developing countries face the challenges of low tax compliance behavior due to the self-assessment system. Therefore, the purpose of this study was to obtain empirical evidence about the implication of early tax education toward the changes in future taxpayers’ compliance behavior. Previous research found that early tax education can develop the compliance paradigm in human behavior. This study employed a quantitative research method with a case study approach. Data was gathered through a survey of 719 students of junior and senior high school in Jakarta, Indonesia as respondents, and divided into two groups: those who receive tax learning at school and those who did not. The results revealed that early tax education positively affects taxpayers’ compliance behavior, especially for those who had received tax learning. This study reports preliminary findings in tax education and fills the gap of research in this area. The research contributes to learning and behavior studies and sheds light on implementing early tax education to resolve non-compliance tax behavior.